ARAHAN PENGEMBANGAN AGROINDUSTRI KARET DALAM PENINGKATAN EKONOMI WILAYAH DI KABUPATEN ROKAN HULU, PROVINSI RIAU - Yeni Selfia; Ernan Rustiadi; Andrea Emma Pravitasari (TATALOKA, 2019)
Abstract: High production of rubber plants in Rokan Hulu district has not significantly contributed yet to increasing the welfare of rubber farmers. This is due to a lack of rubber processing industry, leading to rubber being sold in the form of primary product (fresh sap). Therefore, developing an agro-rubber industry is of capital importance. The purposes of the present study were (1) analyze the marketing margin of rubber gum at each marketing level in Rokan Hulu district; (2) analyze the role of rubber agro-industries in the economics of Kampar and Rokan Hulu regions; (3) develop rubber agro-industry to improve the economics of Rokan Hulu district. The methods used in the present research included analysis of marketing margins, input and output analyses, and AHP (Analytical Hierarchy Process). The results showed that both crumb and smoked rubbers sectors play strategic roles in developing other sectors in Kampar district (DFL, IFL> 1). In addition, it was also observed that the rubber sector tended to use the output of other sectors as production inputs (DBL, IBL> 1). Both crumb and smoked rubbers sectors had great abilities to influence not only the regional output multiplier (multiplier output), but also the income multiplier (income multiplier) (I > 1). However, the ability of the NTB multiplier (multiplier NTB) to improve the sectors was very low (NBT <1). This showed that rubber industry has better development opportunities in Rokan Hulu. The type of rubber processing industry to be developed in Rokan Hulu depends on the perceptions of stakeholders. For instance, a rubber industry that can produce products such as rubber crumb, sheet, Sir 10, and Sir 20. Initial attempts by local government in developing the rubber industry is the increase of qualified, skilled, and reliable human resources to insure optimal functioning of the rubber agro-industry.